Understanding intracardiac EGMs : a patient centered guide - Kusumoto, Fred (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley-Blackwell, 2015)
"This new book, designed as a series of cases, guides readers through the most common disorders, diagnostic and treatment modalities of electrophysiology"--Provided by publisher
Chapter 21 Wide complex tachycardia case 2Chapter 22 Wide complex tachycardia case 3: premature ventricular contractions; Chapter 23 Wide complex tachycardia case 4; Chapter 24 Wide complex tachycardia case 5; Chapter 25 Wide complex tachycardia case 6; Chapter 26 Syncope; Bradycardia; Tachycardia; Chapter 27 Multiple choice questions and answers; Appendix; Index; EULA
Includes index
Keywords: Electrocardiography; Heart -- Electric properties; Electrophysiologic Techniques, Cardiac -- methods; Electrocardiography -- methods; Electronic books; Problems and Exercises